Fostering Qur’anic Character through Virtual Recitation: A Qualitative Study of the Khatam Al-Qur’an Programme at an Indonesian Medical Faculty - Nugraha, Nanu; Syahid, Akhmad; Abdullah, Nuraeni; Arsyad, Yusril Muhammad (Fakultas Sastra - Universitas Muslim Indonesia, 2025)
This study investigates the implementation and impact of Qur’anic recitation completion (khatam Al-Qur’an) activities as a medium for character development among students at the Faculty of Medicine, Universitas Muslim Indonesia (UMI), Makassar. The research is guided by three primary questions: (1) What is the structure of the khatam Al-Qur’an program in the context of student character formation? (2) What character values are cultivated through this activity? and (3) How effective is the implementation of the khatam Al-Qur’an program within the faculty environment? The objective is to analyze the implementation process, identify the character values fostered, and assess the program’s effectiveness in integrating spiritual and professional development among medical students. The activity is held regularly during the holy month of Ramadan and is positioned as a strategic initiative for character education grounded in Islamic spiritual values. A qualitative descriptive approach was employed, using data collected through observations, in-depth interviews, and questionnaires administered to participating students and program facilitators. The results reveal that the program is systematically implemented in both online and offline formats through two main modalities: (1) One Day One Juz (ODOJ), conducted individually, and (2) collective qira’ah sessions, carried out in turns via virtual platforms or face-to-face gatherings. These formats effectively instill core character values such as religiosity, honesty, discipline, responsibility, and inner peace. Students reported that participation in the program significantly enhanced their spiritual well-being, boosted academic motivation, and shaped a strong foundation for ethical professionalism in the medical field. The present study sheds light on the khatam Al-Qur’an program conducted during Ramadan which serves as an effective and integrative tool for character development, bridging spiritual enrichment with academic and professional ethics. The model demonstrates strong potential to be adapted as a sustainable character-building initiative within higher education institutions rooted in Islamic values.